PENGARUH DISIPLIN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT. TATA GUNA PATRIA DI JAKARTA SELATAN - Danianti Manaraja; Angga Juanda (Journal of Research and Publication Innovation, 2025)
This study aims to determine the Influence of Work Discipline and Compensation on Employee Performance at PT Tata Guna Patria, South Jakarta. The method used in this study is the quantitative associative method, Primary and secondary data collection techniques, which are used through questionnaires with a total of 67 respondents, observation, literature study. The analysis method used in this study is the validity test, reliability test, classical assumption test, simple and multiple linear regression test, correlation coefficient test, determination test and significance test (t test and F test). The results of the study showed that the Durbin-Watson value was 1.850 and was between (<1) according to the provisions, so this regression model has autocorrelation. The coefficient of determination value (Adjusted R2) was obtained at 0.400 or 40.0% and the remaining 60.0% was influenced by other factors. It is known that the significant value for the influence of X1 on Y is 0.000 <0.05 and the t-value is 5.805> 1.668, it can be concluded that Ha1 is accepted which means that there is an influence of X1 on Y. It is known that the significant value for the influence of X2 on Y is 0.000 <0.05 and the t-value is 5.532> 1.668, it can be concluded that Ha2 is accepted which means that there is an influence of X2 on Y. The F table value of 2.404 was obtained by looking at the F table with df = k-1 (3-1=2) and df = n-k (67-2=65) at a significance level of 0.05. So it can be concluded that Ho is rejected and Ha is accepted or Work Discipline (X1) and Compensation (X2) together have a large influence on employee performance.